The Test Your Memory for Mild Cognitive Impairment (TYM-MCI) - Brown, Jeremy M (J Neurol Neurosurg Psychiatry, 2017)
BACKGROUND: To validate a short cognitive test: the Test Your Memory for Mild Cognitive Impairment (TYM-MCI) in the diagnosis of patients with amnestic mild cognitive impairment or mild Alzheimer’s disease (aMCI/AD). METHODS: Two hundred and two patients with mild memory problems were recruited. All had ‘passed’ the Mini-Mental State Examination (MMSE). Patients completed the TYM-MCI, the Test Your Memory test (TYM), MMSE and revised Addenbrooke’s Cognitive Examination (ACE-R), had a neurological examination, clinical diagnostics and multidisciplinary team review. RESULTS: As a single test, the TYM-MCI performed as well as the ACE-R in the distinction of patients with aMCI/AD from patients with subjective memory impairment with a sensitivity of 0.79 and specificity of 0.91. Used in combination with the ACE-R, it provided additional value and identified almost all cases of aMCI/AD. The TYM-MCI correctly classified most patients who had equivocal ACE-R scores. Integrated discriminant improvement analysis showed that the TYM-MCI added value to the conventional memory assessment. Patients initially diagnosed as unknown or with subjective memory impairment who were later rediagnosed with aMCI/AD scored poorly on their original TYM-MCI. CONCLUSION: The TYM-MCI is a powerful short cognitive test that examines verbal and visual recall and is a valuable addition to the assessment of patients with aMCI/AD. It is simple and cheap to administer and requires minimal staff time and training.